Applied international finance : managing foreign exchange risk and international capital budgeting - O'Brien, Thomas J. (2014 digital library., 2014)
This text is designed for use in a course in applied international corporate finance for managers and executives. Instead of the "encyclopedic" approach, the text focuses on the two main issues of interest to managers who deal with overseas operations. The first main issue is how uncertain foreign exchange (FX) rate changes affect a firm's ongoing cash flows and equity value, and what can be done about this risk. The second main issue is the estimation of the cost of capital for international operations and the evaluation of overseas investment proposals. Numerous examples of real-world companies are used.